Variasi tipe pelarut dan pengaruhnya terhadap kadar flavonoid total daun kirinyuh (Chromolaena odorata) yang tumbuh di kawasan geotermal Ie Seum Aceh Besar menggunakan spektrofotometri uv-vis - Munira, Munira; Zakiah, Noni; Handayani, Rini; Nasir, Muhammad; Frengki, Frengki (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: One plant that can be a source of natural healing for various ailments is the kirinyuh (Chromolaena odorata). This plant can grow in geothermal areas. Plants grown in geothermal areas have the potential to produce higher levels of active substances. The kirinyuh plant is rich in flavonoid compounds. Flavonoids have antioxidant, anti-inflammatory, antibacterial, antiviral properties, and have potential as anticancer agents. The level and quality of flavonoid compounds are influenced by the type of solvent.Objectives: This study was conducted to determine the total flavonoid content of kirinyuh leaf extract from the Ie Seum geothermal area of Aceh Besar based on different types of solvents.Methods: Determination of total flavonoid content using UV-Vis spectrophotometry and quercetin was used as a standard in the measurement. Each measurement was repeated three times. The results were analyzed using an independent t-test.Results: The results of the determination of total flavonoid levels obtained in kirinyuh leaves using ethanol solvent were 10,65 mg QE/g and ethyl acetate was 8,97 mg QE/g. Based on the results of the Independent T-test, a significance result of 0,000 (P<0,05) was obtained. These results indicate that there is a difference in total flavonoid levels between ethanol and ethyl acetate solvents.Conclusion: The total flavonoid content using ethanol solvent types were higher than ethyl acetate.